Perbaikan Kinerja Rantai Pasok Halal Berdasarkan Pengukuran dengan Model Supply Chain Operation Reference (SCOR) - Xena Vega Analia; Aviasti (Jurnal Riset Teknik Industri, 2021)
Abstract. The industrial sector is experiencing increasingly fierce competition, requiring each company to continue to improve its competitiveness. The competitiveness of the company can be done through improving product quality as well as understanding and fulfilling the needs and desires of consumers. In order to make this happen, it is necessary to pay attention to supply chain activities from upstream to downstream, from selecting suppliers to distribution activities to consumers.X Bakery is one of the food industry sectors in the city of Bandung. In its activities, X Bakery involves several activities, namely procurement activities, manufacturing activities to distribution activities. However, the products produced by X Bakery do not have a halal certificate so it is necessary to check the flow of their supply chain. In their activities, small and medium enterprises are not yet aware of the importance of halal certification in the products they produce, in line with public awareness of halal assurance, the halal supply chain can be a solution to this problem. So that in this study, performance measurement in supply chain activities added several aspects related to the halal concept.The supply chain performance measurement is carried out using the SCOR model approach and the weighting is carried out using the Fuzzy AHP method. Based on the research, it is known that the overall value of the assessment is included in the average category with a value of 69.59. Of the 15 KPIs studied, there are 8 KPIs that are still low. Of the 8 low-value KPI’s, 3 of them are KPI’s with the halal concept, including KPI’s for product storage time, cleanliness of transportation equipment, and product time. Where improvements need to be made in order to improve the company's performance by providing several improvement proposals in order to help improve the performance of the X Bakery company. Abstrak. Sektor industri mengalami persaingan yang semakin ketat menuntut setiap perusahaan agar terus meningkatkan daya saingnya. Daya saing yang dilakukan pada perusahaan dapat melalui peningkatan kualitas produk serta dengan memahami dan memenuhi kebutuhan dan keinginan konsumen. Agar bisa mewujudkan hal tersebut, maka perlu diperhatikan pada kegiatan rantai pasok dari hulu hingga hilir, mulai dari pemilihan supplier hingga pada kegiatan pendistribusian ke konsumen. X Bakery merupakan salah satu sektor industri makanan di Kota Bandung. Dalam kegiatannya X Bakery melibatkan beberapa aktivitas, yaitu aktivitas pengadaan, manufaktur hingga aktivitas distribusi. Namun produk yang dihasilkan X Bakery belum memiliki sertifikat halal sehingga perlu dilakukan pemeriksaan pada aliran rantai pasokmya. Dalam kegiatannya usaha kecil menengah belum sadar akan pentingnya sertifikasi halal pada produk yang dihasilkannya, sejalan dengan meningkatnya kesadaran masyarakat akan jaminan halal, maka dengan mengadopsi halal supply chain dapat menjadi solusi untuk permasalahan tersebut. Sehingga dalam penelitian ini pengukuran kinerja pada aktivitas supply chain yang ditambahkan beberapa aspek terkait dengan konsep halal. Pengukuran kinerja supply chain dilakukan dengan pendekatan model SCOR dan pembobotan dilakukan dengan metode Fuzzy AHP. Berdasarkan hasil penelitian diketahui bahwa nilai keseluruhan penilaian kinerja termasuk pada kategori average dengan nilai 69,59. Dari 15 KPI yang diteliti, terdapat 8 KPI masih memiliki nilai rendah. Pada 8 KPI nilai rendah, 3 diantaranya merupakan KPI dengan konsep halal, yaitu KPI waktu penyimpanan produk, kebersihan alat transportasi, waktu pengembalian produk. Dimana perlu dilakukan perbaikan agar dapat meningkatkan kinerja perusahaan dengan diberikannya beberapa usulan perbaikan agar dapat membantu peningkatan kinerja perusahaan X Bakery.